Equal rites : the Book of Mormon, Masonry, gender, and American culture - Forsberg, Clyde R. (Religion and American culture (New York, N.Y.), 2004)
Both the Prophet Joseph Smith and his Book of Mormon have been characterized as ardently, indeed evangelically, anti-Masonic. Yet in this sweeping social, cultural, and religious history of nineteenth-century Mormonism and its milieu, Clyde Forsberg argues that masonry, like evangelical Christianity, was an essential component of Smith's vision. Smith's ability to imaginatively conjoin the two into a powerful and evocative defense of Christian, or Primitive, Freemasonry was, Forsberg shows, more than anything else responsible for the meteoric rise of Mormonism in the nineteenth century.<b.